Antioxidant Properties of Lapachol and Its Derivatives and Their Ability to Chelate Iron (II) Cation: DFT and QTAIM Studies - Djafarou Ngouh Pajoudoro; Daniel Lissouck; Baruch Ateba Amana; Joseph Zobo Mfomo; A. E. B. Abdallah; Alfred Aristide Flavien Toze; Désiré Bikele Mama (Bioinorganic Chemistry and Applications)
The elucidation of the complexation of lapachol and its derivatives to Fe2+ cation has been done using the density functional theory (DFT). This complexation has been limited to bidentate and tridentate to Fe2+ cation. Geometry optimizations have been implemented in gas and solution phase (water, acetonitrile, chlorobenzene, benzene, and toluene) for ligands at B3LYP/6-311++G (d,p) level of theory using B3LYP/6-31+G(d,p) optimized data as starting point. But, the geometrical optimizations in solution phase of the 22 complexes analyzed of lapachol and its derivatives to Fe2+ cation were restricted to acetonitrile and benzene. The complexation energy and the metal ion affinity (MIA) have also been calculated using the B3LYP method. The results obtained indicated a proportionality between the MIA values and the retained charge on Fe2+ cation for k2-(O1,O2) modes. But, an inverse proportionality has been yielded between these two parameters for k3-(O2, C=C) tridentate modes. For k3-(O3,C=C) tridentate mode coordination, the higher stability has been obtained. In this latter tridentate coordination in gas phase, the topological analysis of complexes exhibits the fact that the electron density is concentrated between the O3 oxygen atom of the ligand attached to Fe2+ and this metal cation. Moreover, the hydrogen bond strength calculated for isolated ligands (situated between 23.92 and 30.15 kJ/mol) is in the range of normal HBs. Collectively, all the complexation processes have shown to be highly exothermic. Our results have also shown that the electron extraction from Fe2+...Lai complexes is more difficult compared to that from free ligands.